Garbage disposal function of household in selected barangays in Jaro, Iloilo City - Esmero, Czarina Catherine E.
The general problem of the study is "Do economic and non-economic variables affect the volume of garbage households dispose in the six barangays within the perimeter of Jaro Plaza, Jaro Iloilo City?" This study has three main objectives: To describe the socio-economic profile of the households in the six barangays within the perimeter of Jaro Plaza in Jaro City; To identify the garbage disposal practices of the same respondents and to determine if the volume of garbage households dispose is affected by the price households pay for garbage disposal services, household income, household size, educational attainment of the head of the family, other services competing with garbage disposal, presence of infants in the household and the presence of household operated business., Some 26.16% of the respondents belong in the income bracket of P76,000 to P100,000 which means that the respondents have a lower annual income relative to the national annual average of P141,000. In this study, 36.63% of the respondents have an average household size of 8-10 members which is larger than that of Iloilo City average of 5 members. With 101 of 172 respondents having graduated from college, which means that the respondents have a lower annual income relative to the national annual average of P141,000. In this study, 36.63% of the respondents have an average household size of 8-10 members which is larger than that of the Iloilo City average of 5 members. With 101 of the 172 respondents having graduated from college, which is 58.70%, it was known that there is high literacy rate in the area of the study. Respondents primarily dispose their garbage through public dump trucks which collects the said garbage in daily. While some garbage are burned, biodegradable wastes such as kitchen left overs are fed to animals. Composting is a minimal activity for reasons of lack of space and that the respondents have no time for it. Very few dump their garbage in a vacant lot and respondents from one particular barangay, which is beside a river, only dump their garbage in a flowing body of water. The coefficient of determination, r squared (r2) that has a value of 0.564250 means that 56.43% of the variations in the dependent variable (volume) is explained by the independent variables used in the model. F-test shows that the independent variables taken as a whole is significant at a=0.01. The test shows cost of garbage disposal, household income, household size, presence of infants in the household and household-operated business significantly affect the volume of garbage the respondents dispose.